CSF3 promotes colorectal cancer progression by activating p65/NF-κB signaling pathway and inducing an immunosuppressive microenvironment - Junfeng Xu; Na Li; Hui Xie; Changwei Duan; Xingchen Liao; Ruoran Li; Heng Zhang; Yuanming Pan; Xianzong Ma; Shuwen Du; Jianqiu Sheng; Xin Wang; et al. (Translational Oncology)
Background: Colony-stimulating factor 3 (CSF3) is a cytokine that promotes inflammation by stimulating the maturation, proliferation, and trafficking of myeloid progenitor cells. However, the functional importance of CSF3 in colorectal cancer (CRC) remains unclear. Methods: CSF3 expression levels in CRC cells and tissues were detected by quantitative real-time PCR (qRT-PCR), western blot and immunohistochemistry (IHC). In vitro and in vivo assays were performed to investigate the oncogenic function of CSF3 in the tumor associated malignant phenotypes and the tumorigenic capability of CRC cells. Immunocoprecipitation was performed to verify the regulatory effects of CSF3 on IκBα ubiquitination. Results: We found that CSF3 was overexpressed in CRC tissues compared to adjacent normal tissues, which correlated with poor patient survival. In vitro, silencing CSF3 significantly impaired cell proliferation, colony formation, and migration, while enhancing apoptosis. In vivo, silencing CSF3 resulted in reduced tumor growth, weight, and volume, indicating its potential as a therapeutic target. Mechanistically, CSF3 was found to mediate CRC development by activating the NF-κB signaling pathway, as evidenced by the decreased phosphorylation of p65 and reduced IκBα ubiquitination in CSF3-silenced cells. Furthermore, CSF3 silencing modulated immune infiltration in CRC, promoting an anti-tumor immune response and altering the tumor microenvironment. Conclusion: CSF3 modulated the NF-κB signaling pathway through a distinct mechanism involving p65 phosphorylation and the activation of NF-κB by enhancing IκBα ubiquitination, thereby effectively promoting CRC development, and CSF3 may serve as a potential therapeutic target for repressing CRC advance and metastasis.